Roasting temperature effect on the recovery of refractory gold and silver in pyrite concentrates - Zhang, Yipeng; Yang, Ke; Fang, Yi; Robledo Cabrera, Aurora; Peng, Changsheng; López-Valdivieso , Alejandro (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Pyrite concentrates with refractory gold and silver were roasted at different temperatures to improve the recovery of the metals by cyanide leaching. SEM characterization of the calcine revealed that the gold occluded in the pyrite less than one micron, and roasting produced channels in the concentrate, exposing the gold particles to the leaching solution. Gold and silver recoveries were maximum in the temperature range of 500-600°C due to the calcine high porosity. The Au and Ag recovery improved from 25 to 86% and 50 to 73%, respectively. Gold secondary encapsulation due to the sintering and formation of silver ferrite in higher roasting temperatures hence recoveries decreased.